The interplay of growth differentiation factor 15 (GDF15) expression and M2 macrophages during prostate carcinogenesis. (2nd July 2020) - Sadasivan, Sudha M; Chen, Yalei; Gupta, Nilesh S; Han, Xiaoxia; Bobbitt, Kevin R; Chitale, Dhananjay A; Williamson, Sean R; Rundle, Andrew G; Tang, Deliang; Rybicki, Benjamin A
Abstract: M2 (tumor-supportive) macrophages may upregulate growth differentiation factor 15 (GDF15), which is highly expressed in prostate tumors, but the combined utility of these markers as prognostic biomarkers are unclear. We retrospectively studied 90 prostate cancer cases that underwent radical prostatectomy as their primary treatment and were followed for biochemical recurrence (BCR). These cases also had a benign prostate biopsy at least 1 year or more before their prostate cancer surgery. Using computer algorithms to analyze digitalized immunohistochemically stained slides, GDF15 expression and the presence of M2 macrophages based on the relative density of CD204- and CD68-positive macrophages were measured in prostate: (i) benign biopsy, (ii) cancer and (iii) tumor-adjacent benign (TAB) tissue. Both M2 macrophages ( P = 0.0004) and GDF15 ( P < 0.0001) showed significant inter-region expression differences. Based on a Cox proportional hazards model, GDF15 expression was not associated with BCR but, in men where GDF15 expression differences between cancer and TAB were highest, the risk of BCR was significantly reduced (hazard ratio = 0.26; 95% confidence interval = 0.09–0.94). In addition, cases with high levels of M2 macrophages in prostate cancer had almost a 5-fold increased risk of BCR ( P = 0.01). Expression of GDF15 in prostate TAB was associated with M2 macrophage levels in both prostate cancer and TAB and appeared to moderate M2-macrophage-associated BCR risk. In summary, the relationship of GDF15 expression and CD204-positive M2 macrophage levels is different in a prostate tumor environment compared with an earlier benign biopsy and, collectively, these markers may predict aggressive disease. Abstract : Growth differentiation factor 15 (GDF15) expression and M2 macrophages levels could play a role in prostate carcinogenesis. Biochemical recurrent disease is associated with high M2 macrophages levels in cancer and GDF15 expression that is lower in cancer compared to adjacent benign prostate.